Dynamic Prediction Model of Multisource Gas Emissions in a Fully Mechanized Top Coal Caving Based on the Coal Particle Size Distribution - Han Gao; Xuanping Gong; Xiaoyu Cheng; Rui Yu (Shock and Vibration)
Coal particle size is an important factor affecting the gas emission law. Taking Wangjialing coal mine as the research object, the particle size distribution of coal mining and caving is analyzed via field tests in order to develop the gas emission theoretical model from granular coal. We also perform the numerical simulation of the coal body and longwall face gas emission characteristics under different particles. Finally, the gas emission rules of coal cutting, caving, longwall face, and goaf in Wangjialing coal mine are analyzed, and the dynamic prediction model, which accounts for the time influence of the coal cutting and coal caving speed based on the particle size distribution characteristics, is derived. Results demonstrate the wide distribution of the coal particle size at Wangjialing coal mine, with a higher proportion of small- and large-sized particles. The smaller the coal particle size, the faster the gas emission and the smaller the desorption ratio of coal at ≥20 mm within 30 min. The comprehensive emission intensity of coal mining and caving can be described by an exponential function. The initial emission intensity of coal mining is observed to exceed that of coal caving, while the attenuation laws of the two are essentially equal, and the majority of the gas emission is completed within 5 min. The error between the results of the multisource dynamic prediction model and the field measurement is small, which is of practical application significance.